Enterprise Innovation In Service Independent Practice Of Midwives In Indonesia : Literature Review - et. al., Eny Yuniati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Midwives perform an innovative and transformation role because they are the primary services closest to the community. Midwives could become HealthPartners, which is one of the innovations in midwifery services they can provide. Midwifery services have implemented entrepreneurship as one of their business innovations. The growing number of midwifery graduates, limited employment opportunities, and competition for high-quality midwifery services have prompted midwives to open their practices and innovate in the field. A specific service product can be created by combining a midwife's characteristics with her ability, knowledge, and skills. This study is a review of the literature on entrepreneurial innovation in Indonesian midwives' self-service. The article is analyzed using Google Schola and two literature reviews that meet the criteria. According to the literature review findings, oxytocin massage, postpartum massage, baby massage, breast massage, perineal massage, and yoga for pregnant women and babies spas are examples of entrepreneurial innovations in self-service for midwives in Indonesia. A midwife's creativity can help her develop new ideas, develop new services and methods, or create a new product in midwifery services that will benefit both mother and baby.